LeFort I Osteotomy - Buchanan, Edward P.; Hyman, Charles H. (Seminars in Plastic Surgery, 2013)
The LeFort I osteotomy is one of the most commonly used procedures to correct midface deformities. It allows for correction in three dimensions including advancement, retrusion, elongation, and shortening. It is indicated, often in conjunction with mandibular surgery, for class II and III malocclusion, facial asymmetry, obstructive sleep apnea, and maxillary atrophy. Before surgery, proper orthodontics and surgical planning should be undertaken to ensure adequate outcomes. Overall, the surgery is widely used due to its low complication profile and reliable long-term results.
Keywords: LeFort I; osteotomy; malocclusion; orthognathic; distraction